Epidemiology of myelin oligodendrocyte glycoprotein antibody-associated disease: a review of prevalence and incidence worldwide - Hor, Jyh Yung; Fujihara, Kazuo (Frontiers in Neurology, 2023)
Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) is an inflammatory demyelinating disease of the central nervous system (CNS) with presence of conformation-sensitive antibodies against MOG. The spectrum of MOGAD includes monophasic/relapsing optic neuritis, myelitis, neuromyelitis optica spectrum disorder (NMOSD) phenotype without aquaporin 4 (AQP4) antibodies, acute/multiphasic demyelinating encephalomyelitis (ADEM/MDEM)-like presentation, and brainstem and cerebral cortical encephalitis. There is no apparent female preponderance in MOGAD, and MOGAD can onset at all age groups (age at onset is around 30 years on average, and about 30% of cases are in pediatric age group). While there have been prevalence and incidence data available for AQP4+ NMOSD globally, such data is only beginning to accumulate for MOGAD. We reviewed the currently available data of population-based MOGAD studies conducted around the world -3 studies in Europe, 3 in Asia, and 1 joint study in the Americas. The prevalence of MOGAD is approximately 1.3 -2.5 / 100,000, and the annual incidence is 3.4 -4.8 / million. Among Whites, the prevalence of MOGAD appears slightly higher than AQP4+ NMOSD. No obvious latitude gradient was observed in the Japanese nationwide survey. Data available so far showed no obvious racial preponderance or strong HLA associations in MOGAD. However, precedent infection was reported in 20-40% of MOGAD cases and this is worthy of further investigation. Co-existing autoimmune disorders are less common in MOGAD than in AQP4+ NMOSD, but NMDAR antibody may occasionally be positive in patients with MOGAD. More population-based studies in different populations and regions are useful to further inform the epidemiology of this disease.